2015
DOI: 10.1556/avet.2015.001
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal distending toxin A, B and C subunit proteins are necessary for the genotoxic effect of Escherichia coli CDT-V

Abstract: Cytolethal distending toxins (CDT) are considered the prototype of inhibitory cyclomodulins, and are produced by a wide range of Gram-negative pathogenic bacteria, including Escherichia coli strains of various sero- and pathotypes. CDT is a heterotripartite toxin consisting of three protein subunits, CdtA, CdtB and CdtC. The active subunit, CdtB has DNase activity and causes DNA damage and cell cycle arrest in the target cell. However, several studies have highlighted different roles for CdtA and CdtC subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
2
1
Order By: Relevance
“…The tripartite model was confirmed despite the fact that CDT-specific phenotypes were reported in some cases in lack of A and / or C subunit. Taieb et al [24] using the same strategy, as in the present study, confirmed that in the case of E . coli CDT-V, as with other investigated CDT types, both CdtA and CdtC are necessary for the toxin to be fully functional [25].…”
Section: Discussionsupporting
confidence: 89%
“…The tripartite model was confirmed despite the fact that CDT-specific phenotypes were reported in some cases in lack of A and / or C subunit. Taieb et al [24] using the same strategy, as in the present study, confirmed that in the case of E . coli CDT-V, as with other investigated CDT types, both CdtA and CdtC are necessary for the toxin to be fully functional [25].…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, but consistent with the lack of an apparent contribution of OMV-associated CdtV-A and CdtV-C to the CdtV-B trafficking, the OMV-delivered recombinant CdtV-B subunit was retrogradely transported via the Golgi complex and the endoplasmic reticulum to the nucleus ( Fig 11C and 11E ), and reproduced all biological effects of CdtV holotoxin including the activation of the DNA damage response, G2 arrest, and cell distension ( Fig 13A–13C ). Although these findings contradict the generally accepted model of cytotoxicity of free Cdts, which requires collaboration of all three Cdt subunits [ 74 , 75 ], they are in agreement with the ability of C . jejuni CdtB to cause the G2 arrest and cell distension when microinjected into the cytoplasm of target cells [ 76 ], a mode of delivery which circumvents the binding roles of CdtA and CdtC, and, plausibly, also their contribution to CdtB retrograde transport.…”
Section: Discussioncontrasting
confidence: 48%
“…Phosphorylation of Cdc25C creates an interaction site for the 14-3-3 family of proteins that sequester Cdc25C in the cytoplasm (Ahn et al, 2004). Thus, phosphatase Cdc25C is unable to activate the nuclear hyper-phosphorylated (inactive) CDK1/cyclin B complex, leading to the delay in the G2/M phase transition of the cell cycle (Taieb et al, 2015). Delay at the G1/S phase by CDT is also reported, and results from an ATM/p53-dependent accumulation of the CDK2-cyclin E inhibitor, p21 Cip1 .…”
Section: Bacterial Cyclomodulinsmentioning
confidence: 99%